Effect of Different Energy Sources on Silage of Dwarf Elephant Grass (Pennisetum Purpureum Cv. Mott) on Digestibility and Rumen Fluid Fermentation Parameters - Insun Sangadji; Christian W. Patty; Jojor Desi Sitorus; Nicodemus Gidion Kilmanun (Postgraduate, University of Mataram, 2023)
The development of mini elephant grass is an alternative in providing forage because this grass is a superior type of grass. This paper informs about the morphological characteristics and their advantages as a source of feed and their processing to meet the needs of ruminant feed from mini elephant grass. Mini elephant grass (Pennisetum purpureum cv. Mott) is easily distinguished from elephant grass (P. purpureum) in terms of its morphology. Mini elephant grass has several advantages compared to elephant grass in terms of fast growth and regrowth, ratio of leaves to stems, protein content and high production of dry matter. This grass can be used in grazing and cut and carry systems. In addition, this grass can be given in the form of silage or dry (hay). Processing mini elephant grass through fermentation technology is recommended when production is abundant, so that it can be utilized during the dry season when forage availability is limited. The use of energy sources of 5% such as rice bran, cassava and sago pulp in odot grass silage results in a better quality of the chemical composition of odot grass silage and can increase KcBK, KcBO, VFA, and rumen fluid pH. While the use of rice bran as an energy source can increase the parameters of NHâ‚ƒ fermentation